Integrating paid work and chronic illness in daily life: A space-time approach to understanding the challenges. (July 2015) - McQuoid, Julia; Welsh, Jennifer; Strazdins, Lyndall; Griffin, Amy L.; Banwell, Cathy
Abstract: The upward trend of chronic illness in working age populations calls for better understanding of the difficulties chronically ill people face with workforce participation. Existing research focuses primarily on physical limitations and employer attitudes about chronic illness. Here we use a space-time approach to illuminate the importance of negotiating logistical challenges and embodied rhythms when balancing work and chronic illness. We draw from time geography and rhythmanalysis in analysing interviews from a qualitative case study of 26 individuals living with chronic kidney disease in Australia. Difficulties with paid work arise from: (1) competition for space-time resources by employers and health services; (2) arrhythmias between the body, work and health services; and (3) the absence of workplace rhythms on which to 'hook' health activities. Implications for workplaces and health services design are discussed. Highlights: A space-time approach explores the challenges of working when chronically ill. Health services and employers compete for participants' space-time resources. Arrhythmias of illness, work and health care make everyday activities difficult. Workplace rhythms can undermine illness management activity performance.